Modeling of water quality of Sungai Maong using Inforworks river simulation software - Penny, Ak Sumok (Universiti Malaysia Sarawak (UNIMAS), 2007)
In this study a modeling technique, the InfoWorks RS software with GIS-based was used to study the water quality of Sungai Maong. A water quality simulation model for Sungai Maong was explored with a focus on predicting the dissolved oxygen (DO) parameter. The model adopted a hydrodynamic flow simulation to capture advection and diffusion due to different flow condition~ The on-site hourly (from 9:00 to 15:00) DO data from seven sampling locations (3rd Mile, lIn Bormill Estate N1, lambatan lIn Keretapi N2, lambatan Metro Park N3, lambatan lIn Stapok N4, 5MB Chung Hua N5, Cabang Sg. Maong Kiri & Kanan N 6 and Kpg. Sg Maong N7) along Sungai Maong were collected in December 2006. The hourly DO data collected is considered as Concentration-Time Boundary pollutants. The data was fed into the model except one station N5 that was selected for validation purposes. The calibration of a decay rate, K oforganic matters was found to be satisfactory at a rate of 0.1 per day. The correlation coefficient of the observed and simulated DO concentration at 5MB Chung Hua Station (N5) was at 0.82 (82%). The low DO readings and the slow decay rate of organic matters indicated that the river is alarmingly unhealthy. The developed model by the means values is deliberately descriptive of the transportation of the DO in response to the decaying components. Hypothetical flow conditions of high and low flow scenarios in Sungai Maong Kiri were tested against the advection and diffusion of the concerned pollutants. For demonstration here, an average day in December was simulated at the urban center of Central Park Station (3rd Miles Area). The results show that the flow conditions had little effects on the DO concentration. The river could be said as being lost ofits ability to self-cleansing.